Biocompatible Magnetic Fluids of Co-Doped Iron Oxide Nanoparticles with Tunable Magnetic Properties - Silvio Dutz; Norbert Buske; Joachim Landers; Christine Gräfe; Heiko Wende; Joachim H. Clement (Nanomaterials, 2020)
Magnetite (Fe3O4) particles with a diameter around 10 nm have a very low coercivity (Hc) and relative remnant magnetization (Mr/Ms), which is unfavorable for magnetic fluid hyperthermia. In contrast, cobalt ferrite (CoFe2O4) particles of the same size have a very high Hc and Mr/Ms, which is magnetically too hard to obtain suitable specific heating power (SHP) in hyperthermia. For the optimization of the magnetic properties, the Fe2+ ions of magnetite were substituted by Co2+ step by step, which results in a Co doped iron oxide inverse spinel with an adjustable Fe2+ substitution degree in the full range of pure iron oxide up to pure cobalt ferrite. The obtained magnetic nanoparticles were characterized regarding their structural and magnetic properties as well as their cell toxicity. The pure iron oxide particles showed an average size of 8 nm, which increased up to 12 nm for the cobalt ferrite. For ferrofluids containing the prepared particles, only a limited dependence of Hc and Mr/Ms on the Co content in the particles was found, which confirms a stable dispersion of the particles within the ferrofluid. For dry particles, a strong correlation between the Co content and the resulting Hc and Mr/Ms was detected. For small substitution degrees, only a slight increase in Hc was found for the increasing Co content, whereas for a substitution of more than 10% of the Fe atoms by Co, a strong linear increase in Hc and Mr/Ms was obtained. Mössbauer spectroscopy revealed predominantly Fe3+ in all samples, while also verifying an ordered magnetic structure with a low to moderate surface spin canting. Relative spectral areas of Mössbauer subspectra indicated a mainly random distribution of Co2+ ions rather than the more pronounced octahedral site-preference of bulk CoFe2O4. Cell vitality studies confirmed no increased toxicity of the Co-doped iron oxide nanoparticles compared to the pure iron oxide ones. Magnetic heating performance was confirmed to be a function of coercivity as well. The here presented non-toxic magnetic nanoparticle system enables the tuning of the magnetic properties of the particles without a remarkable change in particles size. The found heating performance is suitable for magnetic hyperthermia application.